Mitochondrial Phylogenomics of Fagales Provides Insights Into Plant Mitogenome Mosaic Evolution - Feng, Yanlei; Xiang, Xiaoguo; Akhter, Delara; Pan, Ronghui; Fu, Zhixi; Jin, Xiaohua (Frontiers in Plant Science, 2021)
Fagales are an order of woody plants and comprising more than 1100 species, most of which produce economically important timbers, nuts, and fruits. Their nuclear and plastid genomes are well sequenced and provided valuable resources to study their phylogeny, breeding, resistance, etc. However, little is known about the mitochondrial genomes (mitogenomes), which hindering a full understanding of their genome evolution. In this study, we assembled complete mitogenomes of 23 species, covering five of the seven families of Fagales. These mitogenomes had similar gene sets but varied 2.4 times in size. The mitochondrial genes were highly conserved, and their capacity in phylogeny was challenging. The mitogenomic structure was extremely dynamic, and synteny among species was poor. Further analyses of the Fagales mitogenomes revealed extremely mosaic characteristics, with horizontal transfer (HGT)-like sequences from almost all seed plant taxa and even mitoviruses. The largest mitogenome, Carpinus cordata, did not have large amounts of specific sequences but instead contained a high proportion of sequences homologous to other Fagales. Independent and unequal transfers of third-party DNA, including nuclear genome and other resources, may partially account for the HGT-like fragments and unbalanced size expansions observed in Fagales mitogenomes. Supporting this, a mitochondrial plasmid-like of nuclear origin was found in Carpinus. Overall, we deciphered the last genetic materials of Fagales and our large-scale analyses provide new insights into plant mitogenome evolution and size variation.